An exploration of hydration care for nursing home residents living with dementia. (2nd December 2021) - Greene, Carolynn; Wilson, Jennie; Tingle, Alison; Loveday, Heather
Abstract : Background/aims: Older adults residing in nursing homes are vulnerable to dehydration. Residents living with dementia can experience additional challenges, making it difficult to independently consume sufficient fluids. The aim of this study was to describe the experience of hydration care for nursing home residents living with dementia. Methods: Observations of hydration care were conducted between 06:00 and 22:45 on one care home unit. Twenty-two residents with dementia were eligible for observation. Conversations with staff and relatives provided further insights. The data were analysed using thematic analysis. Findings: Hydration care provision was highly routinised with little flexibility. Residents received limited support to express individual choices, and staff missed opportunities to provide drinks. More fluid was consumed when care staff developed strategies to encourage fluid intake. Conclusions: Key factors to optimise hydration care include providing individual support to encourage fluid intake and expression of choice, flexible care routines, and focus on communication and teamworking.